Changes and Diurnal Variation of Visual Quality after Orthokeratology in Myopic Children - Hao-Chen Guo; Wan-Qing Jin; An-Peng Pan; Qin-Mei Wang; Jia Qu; A-Yong Yu (Journal of Ophthalmology)
Purpose. To assess the changes and the diurnal variation of visual quality after orthokeratology in myopic children. Methods. Forty-four eyes of 22 subjects with a mean age of 10.55 ± 1.53 years (8 to 14 years) were enrolled in this prospective study. Their spherical equivalent ranged from −1.25 to −4.25 diopters (D) and astigmatism was less than 1.00 D. Parameters including corneal curvature, ocular objective scatter index (OSI), the modulation transfer function (MTF), root mean square of ocular and corneal wavefront aberrations, and contrast sensitivity function (CSF) were measured before and at two time points during the same day after 1 month of orthokeratology. Results. After orthokeratology, uncorrected visual acuity (UCVA) and spherical equivalent were significantly improved from baseline (P<0.001), and their diurnal variation was not significant (P=0.083,0.568). OSI increased from 0.29 ± 0.15 to 0.65 ± 0.31 (P<0.001). MTF decreased significantly (P<0.01). Corneal curvature and ocular total aberration decreased (P<0.001), while the ocular and corneal higher-order aberration increased significantly (P<0.01). The CSF under photopic condition decreased at 3 cpd (P=0.006) and increased at 18 cpd (P=0.012). The diurnal variation of CSF at 18 cpd under mesopic and high glare conditions and at 12 cpd under photopic condition was significant (P=0.002,0.01,0.017). Conclusions. Orthokeratology can effectively improve UCVA and high spatial frequency CSF by decreasing the low-order aberrations. However, MTF and CSF at low spatial frequency decreased because of the increase of intraocular scattering and high-order aberrations. Meanwhile, CSF at high spatial frequency fluctuates significantly at two times during the same day after 1 month orthokeratology.